ANALYSIS OF EQUATORIAL STATES' SOVEREIGN RIGHTS OVER GEOSTATIONARY ORBIT UNDER OUTER SPACE TREATY - Gunawan, Yordan; Putri, Ayi Leoni; Setya, Putri Nurhaliza Anugerah (Diponegoro Law Review, 2025)
Until 2024, equatorial countries are going to stand for the right to sovereignty and even the right to fair and proportional use of geostationary orbit. Equatorial states, despite their geographical advantages, face unequal access and disadvantages when it comes to the geostationary orbit. The prevailing procedures in place actually pose challenges for these states. This research employs normative legal methods to examine the rights and sovereignty claims of equatorial countries in relation to the utilisation of the geostationary orbit. Based on the findings of this study, it is evident that equatorial countries' assertions of sovereignty lack justification under current international legal frameworks. However, this research also provides a solution to revamp the mechanism for governing the utilisation of geostationary orbits. This solution is built upon the principle of special and differential treatment, which has been adopted by the World Trade Organisation (WTO). By embracing this principle, there is optimism that equatorial countries will have a better chance at accessing the geostationary orbit in a just and balanced manner. This will enable them to fully utilise their geographical advantages while staying within the boundaries of international regulations.